Post-conditioning: Promising answers and more questions - Bracco, David (BioMed Central, 2012)
Volatile anesthetic agents have been used for decades in the peri-operative setting. Data from the past 15 years have shown that pre-injury administration of volatile anesthetic can decrease the impact of ischemia-reperfusion injury on the heart, brain, and kidney. Recent data demonstrated that volatile agents administered shortly after injury can decrease the ischemia-reperfusion injury. Several questions need to be answered to optimize this therapeutic target, but this is a promising era of secondary injury mitigation.